Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ijgo.14284
|View full text |Cite
|
Sign up to set email alerts
|

Safe recovery after cesarean in rural Africa: Technical consensus guidelines for post‐discharge care

Abstract: Despite increasing cesarean rates in Africa, there remain extensive gaps in the standard provision of care after cesarean birth. We present recommendations for discharge instructions to be provided to women following cesarean delivery in Rwanda, particularly rural Rwanda, and with consideration of adaptable guidelines for sub-Saharan Africa, to support recovery during the postpartum period. These guidelines were developed by a Technical Advisory Group comprised of clinical, program, policy, and research expert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Additionally, we found that after C-s, women refrain from eating solid and semisolid foods owing to the belief that eating will cause wound-related complications. In Africa, the typical surgical wound is healed on the third postoperative day to a sufficient extent that a woman is discharged and eating is permitted at any time after surgery when the woman feels hungry 36. The health talk messages emphasise the prevention of potential infections during bathing, dressing and physical activities, as well as the maintenance of nutritious diet with a variety of food groups for safe recovery, the restoration of normal bowel function and the support of breast feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that after C-s, women refrain from eating solid and semisolid foods owing to the belief that eating will cause wound-related complications. In Africa, the typical surgical wound is healed on the third postoperative day to a sufficient extent that a woman is discharged and eating is permitted at any time after surgery when the woman feels hungry 36. The health talk messages emphasise the prevention of potential infections during bathing, dressing and physical activities, as well as the maintenance of nutritious diet with a variety of food groups for safe recovery, the restoration of normal bowel function and the support of breast feeding.…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to developed countries, where home visits and surveillance for post-CS mothers are routinely conducted [ 13 ]. Studies report a complete lack of or less information regarding home care after CS compared to home care after vaginaly delivery [ 23 , 24 ]. The limited available information about home care after CS highly varies among different sources across the region [ 25 ].…”
Section: Introductionmentioning
confidence: 99%